Management and Prevention Strategies for Non-communicable Diseases (NCDs) and Their Risk Factors - Aida Budreviciute; Samar Damiati; Samar Damiati; Dana Khdr Sabir; Kamil Onder; Peter Schuller-Goetzburg; Gediminas Plakys; Agne Katileviciute; Samir Khoja; Rimantas Kodzius; Rimantas Kodzius; Rimantas Kodzius (Frontiers Media S.A., 2020)
Non-communicable diseases (NCDs) are of increasing concern for society and national governments, as well as globally due to their high mortality rate. The main risk factors of NCDs can be classified into the categories of self-management, genetic factors, environmental factors, factors of medical conditions, and socio-demographic factors. The main focus is on the elements of self-management and to reach a consensus about the influence of food on risk management and actions toward the prevention of NCDs at all stages of life. Nutrition interventions are essential in managing the risk of NCDs. As they are of the utmost importance, this review highlights NCDs and their risk factors and outlines several common prevention strategies. We foresee that the best prevention management strategy will include individual (lifestyle management), societal (awareness management), national (health policy decisions), and global (health strategy) elements, with target actions, such as multi-sectoral partnership, knowledge and information management, and innovations. The most effective preventative strategy is the one that leads to changes in lifestyle with respect to diet, physical activities, cessation of smoking, and the control of metabolic disorders.